Inclusive values: Foundations of religious education for multicultural harmonious life - Yusuf Siswantara; Ace Suryadi; Mupid Hidayat; Ganjar Muhammad Ganeswara (KURIOS, 2023)
Harmonious living in a diverse society presents complex challenges due to the potential for significant conflict. Radicalism, intolerance, and social conflict often occur, especially concerning religious pluralism. Educational institutions, which are expected to build the nation's character, are also prone to religion's education labeling. Hence, Christian religious education had two choices: strengthen dogmatic teaching or embrace inclusive values. This research focuses on the importance of inclusive values as the foundation for Christian Religious Education. Through descriptive analysis of various literature, this study discusses the theological basis for inclusive values in the context of the Church and its implications for Christian religious education. The research results show that the value of inclusion is based on the reflection of the incarnation and the example of encountering dialogue, which forms the foundation for inclusive Christian Religious Education.